RUPTURE IN A COLLEMBOLA COMMUNITY STRUCTURE FROM A QUERCUS-ROTUNDIFOLIA LAM FOREST DUE TO THE REAFFORESTATION WITH EUCALYPTUS-GLOBULUS LABILL - SOUSA, J. P.; DAGAMA, M. M. (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1994)
Here we compare Collembola populations from a Quercus rotundifolia forest and an Eucalyptus globulus plantation. The overall analysis of data (using both diversity and similarity measures) have shown clear signs of rupture on the structure of collembola populations, with the fauna associated with the Quercus stand being richer (in exclusive and preferential species) and more abundant than the one connected with the Eucalyptus. Data also reflects the faunal stratification between organic and mineral horizons, with the majority of species being associated with upper soil layers in detriment of mineral horizon. These disruptions may be related to profound alterations of habitat characteristics, particularly the frequent removal of shrub vegetation and leaf layer, result of the forestry practices connected with the preparations and management of the eucalyptus plantation.
The following values have no corresponding Zotero field: pub-location: DEPT UNIV PROFESSIONNEL REVUES SCIENTIFIQUES TECHNIQUE 11 RUE GOSSIN, F-92543 MONTROUGE, FRANCE publisher: GAUTHIER-VILLARS
Keywords: Collembola; EUCALYPTUS; holm-oak; REAFFORESTATION